ANALISIS STRATEGI GURU DALAM MENANAMKAN KARAKTER DISIPLIN SISWA KELAS III DI SDN 93 SINGKAWANG TAHUN AJARAN 2024/2025 - Suparman, Dinul Nurrahimi; Wasis Suprapto; Insan Suwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to: 1) Describe the methods used by teachers at SDN 93 Singkawang to instill disciplined character in grade III students; and 2) Identify the factors that instructors naturally use to support and impede the development of disciplined character in grade III students. Utilizing a qualitative descriptive technique, the research methodology for this study is qualitative. Observations, documentation, and interviews are used as data collecting techniques. The principal, educators, and students served as the study's participants. The teacher's method for helping pupils develop disciplined character is the focus of this study. Findings from the research show that: At SDN 93 Singkawang, grade III pupils are taught disciplined character through four methods by their teachers: a) using role models; b) habituation; c) creating a welcoming environment; and d) education. 2) At SDN 93 Singkawang, the following elements affect the development of disciplined character in grade III students: a) Supporting factors, such as student awareness, teacher and student excitement, and parent-school collaboration. b) Playmates and oneself are the things that inhibit